2003
DOI: 10.1071/wf02059
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of fire danger rating indexes using logistic regression and percentile analysis

Abstract: Methods are presented for analysing the relationship between fire danger rating indexes and fire activity as a means of evaluating the performance of fire danger rating systems. Percentile analysis is used to examine the data itself; logistic regression provides a means for statistical analysis. Ranking of selected items indicates indexes that deserve further assessment using subjective considerations. Methods rely on generally available data: the fire danger index for every day in the fire season, fire discov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
137
0
11

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(148 citation statements)
references
References 0 publications
0
137
0
11
Order By: Relevance
“…Fire danger is 'a general term used to express an assessment of both fixed and variable factors of the fire environment that determine the ease of ignition, rate of spread, difficulty of control, and fire impact; often expressed as an index' (FAO 2005 Keetch et al 1968). Of these, we found a very frequent use of FFMC (Cunningham and Martell 1973;Martell et al 1989;Vega-Garcia et al 1995;Wotton et al 2010;Lee et al 2012;Boulanger et al 2014;Li et al 2014;Beccari et al 2015), DC (Wotton et al 2003(Wotton et al , 2010Carvalho et al 2008;Drever et al 2009;Bedia et al 2014) and DMC (Martell et al 1987;Todd and Kourtz 1991;Wotton et al 2003;Magnussen and Taylor 2012), FWI (Haines et al 1983;Martell et al 1987;Vega-Garcia et al 1996;Carvalho et al 2010;Reineking et al 2010;Ager et al 2014;Beccari et al 2015;Papakosta and Straub 2016), ISI (Haines et al 1970(Haines et al , 1983Vega-Garcia et al 1995;Li et al 2014), FFDI (Bradstock et al 2009;Penman et al 2013;Plucinski 2014;Plucinski et al 2014), KBDI (Prestemon and Butry 2005) and ERC (Andrews et al 2003).…”
Section: Predictors For Short-term Studiesmentioning
confidence: 79%
See 1 more Smart Citation
“…Fire danger is 'a general term used to express an assessment of both fixed and variable factors of the fire environment that determine the ease of ignition, rate of spread, difficulty of control, and fire impact; often expressed as an index' (FAO 2005 Keetch et al 1968). Of these, we found a very frequent use of FFMC (Cunningham and Martell 1973;Martell et al 1989;Vega-Garcia et al 1995;Wotton et al 2010;Lee et al 2012;Boulanger et al 2014;Li et al 2014;Beccari et al 2015), DC (Wotton et al 2003(Wotton et al , 2010Carvalho et al 2008;Drever et al 2009;Bedia et al 2014) and DMC (Martell et al 1987;Todd and Kourtz 1991;Wotton et al 2003;Magnussen and Taylor 2012), FWI (Haines et al 1983;Martell et al 1987;Vega-Garcia et al 1996;Carvalho et al 2010;Reineking et al 2010;Ager et al 2014;Beccari et al 2015;Papakosta and Straub 2016), ISI (Haines et al 1970(Haines et al , 1983Vega-Garcia et al 1995;Li et al 2014), FFDI (Bradstock et al 2009;Penman et al 2013;Plucinski 2014;Plucinski et al 2014), KBDI (Prestemon and Butry 2005) and ERC (Andrews et al 2003).…”
Section: Predictors For Short-term Studiesmentioning
confidence: 79%
“…Accepting that fires are rare events and that rarely more than one fire takes place in the temporal and spatial unit under study allows a binary dependent variable to be used. Fire occurrence can be modelled as absence or presence of fire (coded 0 or 1), and most research papers have focused on this binary prediction of wildfires (Andrews et al 2003;Reineking et al 2010;Zhang et al 2010Zhang et al , 2016Arndt et al 2013;Pan et al 2016). Many HCF occurrence models are probabilistic; their output is the probability that 'at least one fire occurs', ranging from 0 to 1.…”
Section: Spatialising Ignition Datamentioning
confidence: 99%
“…Mandallaz and Ye (1997a,b) and Viegas et al (1999) assessed the performance of various European and Canadian fire danger indices in predicting wildfire activity in southern Europe and the former found that using weather variables and other covariates in addition to a fire danger index could produce substantial improvement in prediction of wildfires. Andrews et al (2003) evaluated the US NFDRS indices and fire activity in the Tonto National Forest in Arizona, finding that a logistic function of ERC predicts wildfire incidence better than a logistic function of BI.…”
Section: Examined the Nfdrs Ignition Component And Spreadmentioning
confidence: 99%
“…Logistic regression is one of the most frequently used methods (Andrews et al 2003, Vasconcelos et al 2001, Chuvieco et al 2003, Amatulli et al 2007, Brosofske et al 2007, Zhang et al 2010. It has been used to develop regional models with a large spatial extent (Chuvieco et al 1999, Martinez et al 2009) as well as for developing models on a local scale (Vega-Garcia et al 1995, Vasconcelos et al 2001.…”
Section: Parameter and Model Selectionmentioning
confidence: 99%